(untitled) (Majalah Kedokteran Bandung, 2021)
Fertilizer industry workers are at risk of developing lung function disorders, especially from exposure to ammonia and urea dust. This study aimed to determine the vital lung capacity of workers at Fertilizer Factory X, Indonesia, and the influencing factors. This was a cross-sectional analytic observational study on 78 workers who work as an ammonia unit operators in the factory area who met the inclusion and exclusion criteria. Sampling was done consecutively from December 2019 to January 2020. Data were collected using a questionnaire while the pulmonary function measurement was performed using spirometry. Research variables included age, length of work, smoking habits, nutritional status, use of Personal Protective Equipment (PPE), and assessment of vital lung capacity. Data were analyzed using the Chi-Square test and the results showed that the vital lung capacity of most respondents was classified as normal (55.1%). There were significant relationships between vital capacity and risk factors for age (p=0.001), length of work (p=0.009), use of PPE (p=0.012), and smoking habits (p=0.020). It is concluded that there is a relationship between vital capacity and age, length of work, use of PPE, and smoking habits in workers of Fertilizer Factory X, Indonesia.